Employment misconduct - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (LexisNexis Malaysia Sdn Bhd, 2016)
Misconduct, the most common ground for dismissal, is related to an employee’s unacceptable behaviour in the workplace that relates to duty, discipline and immorality. Gross misconduct can take many forms, ranging from offences which jeopardise the functioning of the employer’s business or the safety and well-being of the employees. This includes offences such as immorality at the workplace, insolence and insubordination, criminal conduct, or any other conduct inconsistent with the relationship of an employer and employee. Such offence if established empowers the employer to dismiss the affected employee. Offences relating to work and work performance such as poor timekeeping, absenteeism, misuse of workplace facilities, personal appearance and negligence or sub-standard work among others are usually considered minor misconduct. Such offences do not warrant dismissal for a first offence, but may lead to a verbal or written warning, followed by disciplinary hearing if it continues. Repeated minor misconduct such as tardiness, can, cumulatively, result in dismissal. Employer may establish guidelines setting out what constitutes minor or gross misconduct and the mere fact that an employee commits a conduct listed as gross misconduct does not necessarily mean that serious misconduct has occurred. In every case before deciding whether serious misconduct has occurred, the employer must consider all the facts and obtain the employee’s response. In dealing with employee misconduct, employer must heed to the legal framework set by the courts governing the employment misconduct. Courts have consistently held that in order to justify a dismissal, the misconduct must have to be sufficiently serious. Further, the employer must considering all the circumstances in order to determine whether dismissal is an appropriate penalty. Compliant with these guidelines would serve to minimise the risk of litigation for dismissal without just cause or excuse. Hence, this book creates a reference guide to management, supervisors and staff on various forms of misconduct in the workplace, on what to do and how to deal with employee misconduct. It encompasses the concept of misconduct, its classification and the specific categories of gross misconduct namely, misuse of drugs and alcohol, theft, dishonesty, harassment and discrimination towards other employees, customers or the employer, negligence, absenteeism, insubordination, leaking confidential information, internet abuse, and conflict of interest, among others.